Fabrication of a customized impression metal jig for an implant-supported overdenture with a milled bar - Yeganeh Memari; Azadeh Tadayonfard; Amir Fayaz; Elaheh Beyabanaki (Wolters Kluwer Medknow Publications, 2021)
The use of computer-aided design/computer-aided manufacturing technology simplifies the laboratory and clinical steps for the fabrication of implant prostheses. It also reduces additional costs for the prosthetic components and technical procedures. This article describes a modified impression technique using an impression metal jig to enhance the accuracy of final impression and also to eliminate the need for the try-in of resin pattern of the milled bar.